THE INFLUENCES OF TONGUE TWISTER IN TEACHING PRONUNCIATION OF ASPIRATED SOUND [ph] - Kholisoh, Anik; Farida, Alief Noor (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2018)
Speaking English for Indonesian students needs more than an effort to master asthey cannot produce intelligibly pronunciation. Besides, their mother tongueinterferes them when there is different sound production between Indonesian andEnglish; hence, they have difficulty in pronouncing aspirated sound that does notexist in Indonesian. This study aims to find out how Indonesian students pronounceaspirated sound [ph] and the influences of tongue twister to teach pronunciation ofaspirated sound [ph]. This research uses pre-test post-test quasi-experimental design.The data were collected from the result of pronunciation tests of seventh graders ofSMP Negeri 12 Magelang in academic year 2016/2017. The findings showed thatstudents mispronounced [ph] into /p/ as what they had in Indonesian. After beingtaught with tongue twister, the mean score of experiment group increased from13.28 to 50.16. There was significant difference of the ability between students whowere taught pronunciation using tongue twister and those who were not. The t-testresult was 0.000 sig 5%; it means there was different ability between control andexperiment group after receiving the treatment. Based on the result, the researcherconcluded that tongue twister helps Indonesian students to improve theirpronunciation of aspirated sound [ph].